Analysis of market equilibrium based on overconfidence behavior of market makers - Ruohan Wang; Jing Wang; Zhi Yang (PLoS ONE, 2026)
This paper constructs a theoretical model that includes heterogeneous risk-attitude insider traders (risk-neutral and risk-averse), overconfident market makers, and noise traders. It compares the model with two single-risk-attitude models. It systematically studies the impact mechanism of market makers’ overconfidence behavior on market equilibrium. The paper focuses on the influence of the degree of market makers’ overconfidence on market liquidity and the effect of heterogeneous risk attitudes on market stability. The study finds that in the heterogeneous risk-attitude insider trading model, market liquidity λ decreases within a specific range as the market maker’s confidence level k increases. Within another range, market liquidity λ increases as the confidence level k increases. Through comparative analysis of the three models, it is found that insider traders in the heterogeneous risk-attitude model can more actively use private information for trading, and their trading intensity and profit level are significantly higher than those of traders in the single-risk-attitude model. At the same time, the market’s residual information is less. This indicates that the aggressive strategy of risk-neutral insider traders and the conservative behavior of risk-averse insider traders form a complementary effect, which not only buffers the price impact of significant transactions but also promotes the efficient integration of information through diversified order flows. The numerical simulation results further confirm that market makers’ overconfidence will strengthen the information advantage of insider traders. In contrast, the differentiation of insider traders’ risk attitudes optimises the market’s information digestion mechanism, ultimately improving the efficiency of price formation.